AUDITOR INDUSTRY SPECIALISATION IN MALAYSIA - Azham Md. Ali; Mohd. Hadafi Sahdan; Mohd. Hadzrami Harun Rasit (Indonesian Management and Accounting Research, 2007)
By applying audit firm industry market share measure as proxy for audit firm industry expertise or specialisation, the focus in this study is on trends in industry specialisation from 1999 to 2002. With data coming from annual reports of companies listed at the Kuala Lumpur Stock Exchange (KLSE now, Bursa Malaysia) and industry specialists defined as market leaders with market share greater than 20 percent of audit services (in terms of the number of clients) within a client specific industry, it is found that Ernst and Young specialising in construction and plantation, KPMG in industrial products, PricewaterhouseCoopers in finance and Arthur Andersen in finance, plantation, technology and trading/services. Keywords: Auditor Industry Specialisation, Market Share, Big 5, Kuala Lumpur Stock Exchange